1991
DOI: 10.1037/0021-9010.76.6.803
|View full text |Cite
|
Sign up to set email alerts
|

Member competence, group interaction, and group decision making: A longitudinal study.

Abstract: The primary objective of this study was to examine the extent to which increased experience in working in a group would affect group versus individual problem solving. The duration and intensity of group involvement for subjects (over 30 hr) was extensive. In addition, the reward system provided a clear and direct tie between individual or group performance and a significant outcome (i.e., course grades). The decision-making task had a great deal in common with many of the aspects of group decision making in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(142 citation statements)
references
References 33 publications
5
135
0
2
Order By: Relevance
“…The method used had the advantage of allowing close control and better measurement of performance than could have been attained in a business setting, and the reality of the situation in the students' lives provided better confidence in generalizability than could be had in a laboratory setting. Classroom studies of human resource principles have been used successfully in previous research as well (e.g., Tenbrunsel, 1998;Watson, Michaelsen, & Sharp, 1991), and the measurement properties of and attitudinal responses to classroom use of peer evaluations have also been reported elsewhere (MorahanMartin, 1996;Topping, 1998). A possible threat to external validity, however, is the relatively homogeneous age of participants: Most are in their early 20s.…”
Section: Discussionmentioning
confidence: 93%
“…The method used had the advantage of allowing close control and better measurement of performance than could have been attained in a business setting, and the reality of the situation in the students' lives provided better confidence in generalizability than could be had in a laboratory setting. Classroom studies of human resource principles have been used successfully in previous research as well (e.g., Tenbrunsel, 1998;Watson, Michaelsen, & Sharp, 1991), and the measurement properties of and attitudinal responses to classroom use of peer evaluations have also been reported elsewhere (MorahanMartin, 1996;Topping, 1998). A possible threat to external validity, however, is the relatively homogeneous age of participants: Most are in their early 20s.…”
Section: Discussionmentioning
confidence: 93%
“…The way my colleague and I (Shepherd and Haynie 2009a) conceptualized synergies' role regarding conflicting micro-identities is equivalent to how organization scholars describe the relationship between people, groups, and performance. This stream of research has shown that when synergies exist between members of a specific group, the group's overall performance will exceed the sum of each group member's individual performances (Watson et al 1991). Along these same lines, we propose that at the microidentity level, synergies between identities both "broaden" and "raise" the super-ordinate identity curve.…”
Section: Fig 54 Integration Of Micro-identitiesmentioning
confidence: 91%
“…While there are numerous examples of complex tasks involving dyads and larger groups within psychology literature, the tasks in these studies are quite unlike a simple auditing task, and the studies focus on interaction between group members in less well-specified tasks, such as decision making or the learning of complex procedures (e.g., Webb, 1982;Watson, Michaelsen, and Sharp, 1991). A search of the applied psychology literature revealed no laboratory research utilizing groups for similar clerical or counting tasks.…”
Section: Measuring Usabilitymentioning
confidence: 99%